The Composition of Nitrogen-Fixing Microorganisms Correlates With Soil Nitrogen Content During Reforestation: A Comparison Between Legume and Non-legume Plantations - Chen, Jie; Shen, Weijun; Xu, Han; Li, Yide; Luo, Tushou (Frontiers in Microbiology, 2019)
Numerous reforestation projects have been conducted to improve soil fertility in degraded forests, often causing alterations to the soil microbial communities. However, it remains unclear whether microbial functional groups are affected and how these groups correlate with an increase in the nutrient contents during reforestation. We investigated the abundance and composition of free-living nitrogen-fixing microorganisms (diazotrophs) by quantifying and sequencing the marker gene nifH in bulk soils from five reforestation approaches, including legumes and non-legumes, in subtropical China. The relationships between diazotrophic community attributes and soil nitrogen (N) content (NO3−, NH4+ and microbial biomass N) were examined under various approaches. Abundance of diazotrophs was highest in the native tree plantation (Schima spp. and Michelia macclurei) and Acacia mangium monoculture (AM), and lowest in the Pinus massoniana monoculture. The diazotrophic abundance correlated positively with soil organic matter and water content while there was a negative correlation to pH. The composition of diazotrophic community differed significantly among the five reforestation approaches examined and was closely correlated with variations in soil pH, NH4+ and water content. Diazotrophic community composition was closely related to soil NH4+ content, whereas abundance was not. The AM contained higher NH4+, NO3− and microbial biomass N contents than the other reforestation approaches, which may be associated with the indicator species of diazotrophs (Actinobacteria, Proteobacteria and Firmicutes). However, there were more indicator species of Proteobacteria in the mixed Acacia plantation (Acacia mangium and Acacia crassicarpa) than in AM, which might have contributed to the remarkedly lower N content compared to AM. Overall, the soil N content under reforestation appeared to be more related to the composition of diazotroph community than to the abundance of diazotrophs.